Assessment of Scleral and Conjunctival Thickness of the Eye after Ultrasound Ciliary Plasty - Bartłomiej Bolek; Adam Wylęgała; Edward Wylęgała (Journal of Ophthalmology)
Purpose. This study aims to assess scleral and conjunctival thickness using optical coherence tomography after ultrasound ciliary plasty (UCP) procedure with reference to scleral marks appearing in the area where the ultrasound energy was applied. Materials and Methods. Seventy-eight patients with primary and secondary refractory glaucoma participated in this study. Complete ophthalmic examinations including measurements of scleral and conjunctival thickness were performed preoperatively and at 1 week, and 1, 3, 6, 12, 18, and 24 months postoperatively. The parameters were determined using the Swept Source OCT with anterior attachment. Thirty-eight patients (58 scleral marks—23 superior and 35 inferior) fulfilled the inclusion criteria and completed the follow-up period of 24 months. Results. The mean ± SD scleral and conjunctival thickness in superior scleral mark before the procedure and at 1 week, and 1, 3, 6, 12, 18, and 24 months after the procedure was 684.57 ± 83.58 μm, 771.78 ± 112.03 μm (p<0.001), 771.74 ± 100.12 μm (p<0.001), 731.38 ± 83.92 μm (p=0.012), 719.52 ± 73.20 μm (p=0.037), 702.91 ± 66.50 μm (p=0.247), 694.13 ± 72.22 μm (p=0.482), and 699.35 ± 70.68 μm (p=0.200), respectively. The mean ± SD scleral and conjunctival thickness in inferior scleral mark before the procedure and at 1 week, and 1, 3, 6, 12, 18, and 24 months after the procedure was 816.86 ± 79.30 μm, 936.37 ± 107.33 μm (p<0.001), 946.00 ± 130.40 μm (p<0.001), 896.63 ± 123.40 μm (p<0.001), 877.69 ± 114.38 μm (p=0.003), 843.03 ± 71.55 μm (p=0.021), 811.86 ± 68.91 μm (p=0.731), and 805.03 ± 69.52 μm (p=0.248), respectively. The transient thickening of the sclera was observed after the procedure; however, after 12 months postoperatively, the parameters returned to the initial value and no significant difference was noted. Conclusion. The sclera thickness increases after UCP. However, with time the thickness reduces to its initial value with no significant difference. Clinical implication of the scleral changes lasts shorter than the measured significant difference in scleral thickness.